(untitled) (Bangladesh Journal of Microbiology, 2020)
Majority of the population of Bangladesh depend on tap or surface water as their source of water supply. This study was carried out to examine the microbial quality of both water and soil collected from different places using the multiple tube fermentation technique to determine coliform count by the most probable number (MPN) method in brilliant green lactose broth (BGLB) media.Inoculum from positive tubes of the presumptive test were further transferred on eosinemethylene blue (EMB) and MacConkey agar.The organisms isolated were further characterized using biochemical tests. Out of 93 water samples, 30 (32.26%) indicated the presence of lactose fermenter and gas producer in all 3 tubes of dilution series using inoculum quantities of 1.0, 0.1 and 0.01 ml, whereas out of 85 soil samples, 45 (52.94%) showed acid and gas production in all 3 tubes of dilution series.Among 85 soil samples, 40 samples that contained at least one positive in each dilution series and among 93 water samples, 31 samples that contained at least one positive in each dilution series were further re-identified with biochemical tests.This study showed 30.59% soil isolates and 26.88% water isolates were Escherichia coli which highlighted the fact that both water and soil act as a major reservoir of E.coli, which indicates possible fecal contamination as well as presence of potentially pathogenic E. coli. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 75-77